Economics of adult education and training. - TUIJNMAN, Albert C (1997)
Discusses costs and finance, educational production, labour markets and adult education, manpower requirements, employment and unemployment, productivity and economic competitiveness, and the private and social rates of return to investment in adult education and industry training.